Assessing the Climatic Risks of Irrigation Developments in the Nariarle Sub-Watershed in Koubri, Nakanbé Basin, Burkina Faso - Sampebgo Abdoul-Azize; Ouedraogo Ibrahim; Bonkoungou Joachim (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
Climate change is a universal phenomenon, no country is spared, from the richest to the poorest. Irrigation schemes in the Nariarlé sub-watershed, Nakanbé basin in Burkina Faso are exposed to climate risks. These risks are accentuated by the combination of several natural, biophysical, and anthropogenic factors. The objective of this study is to assess the climatic risks of developments in Burkina Faso. The absence of a previous study of the risk assessment of the basin highlights the originality of this article. Documentary research and satellite image processing were used as a methodology. This methodology is supported by field surveys of 160 farmers, questionnaires, and interview guides. Three (03) variables are used to analyze the practices and techniques of adaptation to climate risks of irrigation developments in the Nariarlé watershed (Prevention or anticipation, reduction or resilience, monitoring, and evaluation). The climate analysis shows a change in minimum and maximum temperatures and a persistence of deficit years. The climate risks identified are risks of vulnerability to climatic hazards (water stress, soil erodibility, flooding of irrigated areas, heat waves), risks of exposure (demographic pressure, increase in the level of CO2 content of developments, economic deficit). Climate risk assessment is a tool for decision-making, guidance, practices, and effective adaptation techniques. It is also necessary to strengthen the availability and management of water resources through better monitoring of hydraulic infrastructure, rehabilitation, and integration of groundwater pumping systems using solar panels.